DETERMINANTS OF VILLAGE FUND ACCOUNTABILITY IN FINANCIAL MANAGEMENT OF VILLAGE FUNDS IN PANTAI LABU DISTRICT, DELI SERDANG - Yusri; Chairina; Alya Nurul Assyfa Ginting (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Village funds that are quite large in number must be managed properly by the village government. However, there are indications of low accountability in the management and reporting of village funds by the village government. The purpose of this study was to analyze what factors influence the accountability of village fund financial management in Pantai Labu District, from the following four indicators: technical guidance, presentation of financial reports, perceptions of understanding of main tasks and management commitment. The urgency of the research results is as an evaluation material for the village administration and also to find out the obstacles in implementing village fund management accountability. This study uses SPSS to measure regression, correlation, and variable reliability testing. The hypothesis will be tested with SPSS which aims to examine the relationships between the four variables in this research model. The results of the research implementation show that together they influence the dependent variable, namely the Accountability of Village Fund Financial Management. Partially, 1) Technical Guidance has no effect on the accountability of Village Fund Financial Management, 2) Understanding of Main Tasks has no effect on the accountability of Village Fund Financial Management, 3) Management Commitment has an effect on Accountability of Village Fund Financial Management and 4) Presentation of Financial Statements has an effect on Accountability Village Fund Financial Management.